Benjamin Franklin : inventing America - Gaustad, Edwin S. (Edwin Scott) (Oxford portraits., 2004)
Writer, inventor, diplomat, businessman, musician, scientist, humorist, and civic leader are only a few of the hats Franklin wore. Edwin S. Gaustad presents a balanced account of Franklin's life, emphasizing Franklin's character and personality and quoting extensively from Franklin's own writings.